8.9k views
4 votes
In order to solve for the variable in the equation 2 (x + 3) + 5 x = 3 (2 x minus 1), Jaleesa begins by applying the distributive property, then combines like terms. Which equation is the result of these steps?

7 x + 6 = 6 x minus 3
2 x + 6 + 5 x = 6 x minus 3
2 x + 3 + 5 x = 6 x minus 1
7 x + 3 = 6 x minus 1

User Ishan Shah
by
7.8k points

1 Answer

3 votes

Answer:

7x + 6 = 6x - 3

Explanation:

2(x+3) + 5x = 3(2x-1)

Distribute

2x + 6 + 5x = 6x - 3

Combine like terms

7x + 6 = 6x - 3

hope this helps

User Nicolas Widart
by
7.6k points